The Influence of Artificial Intelligence and Digital Literacy on Repurchase Intention Through Customer Satisfaction Among Tokopedia Users - Vincent Williamson (AKUNTANSI 45, 2025)
The advancement of digital technology has accelerated the adoption of Artificial Intelligence (AI) across e-commerce platforms. Tokopedia, one of Indonesia’s largest marketplaces, has implemented AI features such as chatbots and recommendation systems to improve user experience. However, the effectiveness of AI in driving customer satisfaction and loyalty remains contested. This study investigates the impact of AI-based system quality, information quality, and service quality on customer satisfaction and its effect on repurchase intention. Digital literacy is also examined as an independent variable influencing user satisfaction. The DeLone & McLean IS Success Model serves as the theoretical framework, using a quantitative approach and multiple linear regression analysis on data from 135 Tokopedia users. The results show that system, information, and service quality significantly affect satisfaction, while digital literacy does not. Customer satisfaction positively influences repurchase intention and mediates the relationship between information quality and repurchase intention. This study contributes theoretically by applying the IS Success Model to an AI-driven e-commerce context and offers practical insights for enhancing user-centric and inclusive digital service design.